Greenwashing Awareness, Consumer Behavior, and Energy-Efficient Appliances: An Expansion of The Theory of Planned Behavior - Minh Tran; Toan Le Vu (Journal of Digital Scholarship in Archives and Information, 2026)
Background: Under the urgency of escalating environmental degradation and climate change, understanding consumer behavior toward sustainable products has become increasingly critical. One important decision is the choice of energy-efficient appliances, which directly impacts household energy consumption and national energy security.Aims: This study extends the Theory of Planned Behavior by incorporating green skepticism to examine its influence on university students' purchase intentions for energy-efficient appliances in Hanoi, Vietnam.Methods: A quantitative survey was conducted with 239 students across multiple universities in Hanoi. The proposed model was tested using partial least squares structural equation modeling.Results: The findings reveal that attitude exerts the strongest influence on purchase intention. Green skepticism negatively affects attitude but does not directly deter purchase intention, operating instead through an indirect pathway via attitude. The extended model explains 48.4% of the variance in purchase intention and 62.7% in purchase behavior.Conclusions: These results provide a foundation for policymakers to strengthen green labeling regulations, improve consumer education initiatives, and implement targeted strategies addressing both skepticism and attitude development to promote sustainable consumption practices.